2004
DOI: 10.1128/jb.186.14.4813-4817.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Analysis of the groES - groEL1 , groEL2 , and dnaK genes in Corynebacterium glutamicum : Characterization of Heat Shock-Induced Promoters

Abstract: The appropriate conditions to switch on the heat shock promoters in Corynebacterium glutamicum were defined by Northern blot analysis. Transcriptional patterns were characterized for the groEL2 gene and the groES-groEL1 and dnaK operons. Transcriptional start points of these genes were determined by primer extension analysis, allowing the identification of CIRCE and HAIR boxes close to the ؊10 and ؊35 regions of the promoters. The presence of both CIRCE and HAIR sequences within a single promoter (P-groEL2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…To confirm that the selected heat conditions based on transcriptional studies result in significant changes in the heat shock-induced proteins, anti-DnaK and anti-GroEL antibodies were used to probe total C. glutamicum proteins. Results showed that heating at 40°C for 60 min is adequate for observing the complete heat shock response in the proteome and correlates well with the changes observed at the transcriptional level (3).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…To confirm that the selected heat conditions based on transcriptional studies result in significant changes in the heat shock-induced proteins, anti-DnaK and anti-GroEL antibodies were used to probe total C. glutamicum proteins. Results showed that heating at 40°C for 60 min is adequate for observing the complete heat shock response in the proteome and correlates well with the changes observed at the transcriptional level (3).…”
Section: Resultsmentioning
confidence: 59%
“…Our results showed that two proteins, DnaK and GrpE, which are translated from the same transcripts (dnaK-grpEdnaJ-hspR and dnaK-grpE [3]), occur in very different amounts in the proteome (Fig. 1), indicating the existence of posttranscriptional controls affecting the synthesis or degradation of GrpE compared to that of DnaK.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Chaperonin proteins are found in almost all organisms (if not all) (Braig, 1998) and are classified into six families: Hsp10, Hsp40, Hsp60, Hsp70, Hsp90, and Hsp100. However, in prokaryotes, the HSPs most characterized are hsp60 (groEL), hsp70 (dnaK) and hsp10 (groES) (Eom et al, 2005), and in the Corynebacterium genus two paralogue genes of hsp60 have been described (Barreiro et al, 2004).…”
Section: Heat Shock Proteins: Chaperonin Immunogenicity and Vaccine Dmentioning
confidence: 99%
“…These genes are groES, groEL, dnaJ, grpE, and clpB, which encode chaperones and hspR, which encodes a transcriptional regulator of the heat shock response system (3,12,67). Moreover, four genes that encode hypothetical proteins, as well as a putative starvation-induced, DNA-protecting protein, were found to be differentially expressed (Table 1, genes with other functions).…”
Section: Resultsmentioning
confidence: 99%